2022
DOI: 10.1101/2022.05.30.494054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved transcriptional programming across sex and species after peripheral nerve injury predicts treatments for neuropathic pain

Abstract: Chronic pain is a devastating problem affecting 1 in 5 individuals around the globe, with neuropathic pain the most debilitating and poorly treated type of chronic pain. Advances in transcriptomics and data mining have contributed to cataloging diverse cellular pathways and transcriptomic alterations in response to peripheral nerve injury but have focused on phenomenology and classifying transcriptomic responses. Here, with the goal of identifying new types of pain-relieving agents, we compared transcription… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Is the upregulation in IBA1 labelling induced by SNI due to altered Orai1 expression? Despite the evidence for involvement of Orai1 in mitigating pain hypersensitivity and reducing microglial reactivity in male mice, RNA-seq analysis of the lumbar spinal cord ( 80 ) indicated that SNI did not evoke changes in the expression of Orai1 nor in the expression of other SOCE molecules including Orai2, STIM1, and STIM2 (Figure S10) . Similarly, no change in expression of the SOCE transcriptome was detected in female mice (Figure S10) .…”
Section: Resultsmentioning
confidence: 95%
“…Is the upregulation in IBA1 labelling induced by SNI due to altered Orai1 expression? Despite the evidence for involvement of Orai1 in mitigating pain hypersensitivity and reducing microglial reactivity in male mice, RNA-seq analysis of the lumbar spinal cord ( 80 ) indicated that SNI did not evoke changes in the expression of Orai1 nor in the expression of other SOCE molecules including Orai2, STIM1, and STIM2 (Figure S10) . Similarly, no change in expression of the SOCE transcriptome was detected in female mice (Figure S10) .…”
Section: Resultsmentioning
confidence: 95%
“…The top hit from this analysis was fostamatinib, which targets the nonreceptor tyrosine kinase Syk. Administrating the active metabolite of fostamatinib, R406, intrathecally significantly reversed SNI-induced pain hypersensitivity in both sexes (112).…”
Section: Transcriptomementioning
confidence: 95%
“…Studies of PNI-induced transcriptomic changes are often focused on sex differences, but many of the DEGs are similar between the sexes. A cross-species, cross-sex study investigating spinal cord transcriptomes after SNI from mice and rats of both sexes revealed an overall positive correlation between the sexes in both species (112). The PNI-induced transcriptional reprogramming imputed commonalities, as well as differences, in cellular pathways and gene regulation.…”
Section: Transcriptomementioning
confidence: 99%
“…RNA-seq analysis of spinal tissue from male and female mice is described in a companion study (52). Briefly, the L4-L5 lumbar dorsal horn of the spinal cord was harvested on postoperative day 7 to study transcriptional changes in dorsal spinal tissue.…”
Section: Rna-seq Analysismentioning
confidence: 99%
“…Genes with adjusted P values <0.01 and fold changes greater than 0.5 were defined as differentially expressed genes. A total of 24 samples from mice were analyzed [divided between the Sham-ipsi, Sham-contra, and SNI_ipsi groups; see (52)].…”
Section: Rna-seq Analysismentioning
confidence: 99%